Dissolved Oxygen Availability on Traditional Pond Using Silvofishery Pattern in Mahakam Delta - Ismail Fahmy Almadi; S Supriharyono; Azis Nur Bambang (International Journal of Science and Engineering, 2013)
The development of aquaculture system should meet the community’s basic need economically by taking into account the carrying capacity and environmental sustainability. The development of the environmentally friendly system such as silvofishery is being promoted by government however its yield has not reached the target yet. Dissolved oxygen availability is an important indicator which determines the success of the aquaculture system. The objective of the research was to determine dissolved oxygen availability on traditional pond systems using silvofishery pattern. Time series data collection was conducted once in 14 days with 2 measuring times; in the morning (06.00 am) and in the evening (06.00 pm) for 112 days. The research was conducted at four different silvofishery pond patterns, Pond Pattern 1 (0% mangrove canopy covered), Pond Pattern 2 (35% mangrove canopy covered), Pond Pattern 3 (67% mangrove canopy covered), and Pond Pattern 4 (75% mangrove canopy covered). Measurement was observed openly in the pond (in situ) with parameters: dissolved oxygen, temperature, Water pH, Salinity, Transparency, Wind Speed, and Depth of Water Table, while chlorofil-a was ex-situ measured. The result from each parameter was compared to optimum concentration rate for shrimp growth. From the experiment, Pond Pattern 1 showed the most satisfaction results. Its dissolved oxygen availability during the research was ≥ 4 mg/L which was 5.88 mg/L ±0.48 mg/L in the evening (06.00 pm) and 4.33 mg/L ±1.24 mg/L in the morning (06.00 am). It was also supported by optimum condition of other parameters such as temperature, Water pH, Salinity, Wind Speed, and Depth of Water Table. However, it was not supported by fertility and transparency of water. Thus, the traditional pattern of conservation still needs additional technology to maintain adequate dissolved oxygen availability for optimum shrimp growth.